A Comparative study on the biology of two subspecies of tree squirrels, Paraxerus palliatus tongensis, Roberts, 1931 and Paraxerus palliatus ornatus (Gray, 1864) in Zululand - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2022)
Thesis (DSc (Zoology))--University of Pretoria, 1980.